Rendahnya mutupendidikan tinggi indonesia: Penyebab Dan Strategi Peningkatannya - Sumarno ' (Jurnal Pendidikan, 2012)
Quality ofIndonesianHigher Educationis low, the evidence of which:UnemploymentgraduatesbyAugust 2011is737,030people (BPS RI, 2011); rankingIndonesian highereducationglobally is below, where according to the THE-QS World University Ranking, University ofIndonesia (rankedhighestinIndonesia)in 2011was ranked217of the 600best universitiesin the world;rankedUniversity of Gadjah Mada is 321; InstitutTeknologi Bandungrank401 (Ditjen DiktiKemendiknas, 2011).The lowquality mainly due togovernment'slack of commitmentto education, andleadership andmanagementof higher education thathave not beenbasedon the valuesofacademicquality.Consequence is a lowerquality ofinputs(curriculum, faculty, funding, andinfrastructure). Then theresultto thelow quality oftheeducation, research, community service,andprocess managementand governance.The finalresultis the lowquality ofoutputs and outcomes.Toimprove thequality, the governmentshould increaseits commitment to: the establishmentandimplementation of policies/regulationsand the provision ofeducationandthe allocation of funds. Inaddition,the selection ofthe leaderof thetop-level(Rector/Director) to lower levels(Chairman ofProdi/Labor) must be based onvalues-based academicquality.